Regulation of the Pancreatic Exocrine Differentiation Program and Morphogenesis by Onecut 1/Hnf6Summary - Peter A. Kropp; Xiaodong Zhu; Maureen Gannon (Cellular and Molecular Gastroenterology and Hepatology, 2019)
Background & Aims: The Onecut 1 transcription factor (Oc1, a.k.a. HNF6) promotes differentiation of endocrine and duct cells of the pancreas; however, it has no known role in acinar cell differentiation. We sought to better understand the role of Oc1 in exocrine pancreas development and to identify its direct transcriptional targets. Methods: Pancreata from Oc1Δpanc (Oc1fl/fl;Pdx1-Cre) mouse embryos and neonates were analyzed morphologically. High-throughput RNA-sequencing was performed on control and Oc1-deficient pancreas; chromatin immunoprecipitation sequencing was performed on wild-type embryonic mouse pancreata to identify direct Oc1 transcriptional targets. Immunofluorescence labeling was used to confirm the RNA-sequencing /chromatin immunoprecipitation sequencing results and to further investigate the effects of Oc1 loss on acinar cells. Results: Loss of Oc1 from the developing pancreatic epithelium resulted in disrupted duct and acinar cell development. RNA-sequencing revealed decreased expression of acinar cell regulatory factors (Nr5a2, Ptf1a, Gata4, Mist1) and functional genes (Amylase, Cpa1, Prss1, Spink1) at embryonic day (e) 18.5 in Oc1Δpanc samples. Approximately 1000 of the altered genes were also identified as direct Oc1 targets by chromatin immunoprecipitation sequencing, including most of the previously noted genes. By immunolabeling, we confirmed that Amylase, Mist1, and GATA4 protein levels are significantly decreased by P2, and Spink1 protein levels were significantly reduced and mislocalized. The pancreatic duct regulatory factors Hnf1β and FoxA2 were also identified as direct Oc1 targets. Conclusions: These findings confirm that Oc1 is an important regulator of both duct and acinar cell development in the embryonic pancreas. Novel transcriptional targets of Oc1 have now been identified and provide clarity into the mechanisms of Oc1 transcriptional regulation in the developing exocrine pancreas. Oc1 can now be included in the gene-regulatory network of acinar cell regulatory genes. Oc1 regulates other acinar cell regulatory factors and acinar cell functional genes directly, and it can also regulate some acinar cell regulatory factors (eg, Mist1) indirectly. Oc1 therefore plays an important role in acinar cell development. Keywords: Pancreas Development, Exocrine, Transcriptome